Natural Variational Patterns of some Metrical Characters in Dioscorea deltoidea Wall., Populations in Jammu and Kashmir - Bindroo, B. B.; Bhat, B. K. (Indian Forester, 1986)
The general variation pattern in a number of metrical characters including diosgenin content in tubers of Dioscorca deltoidea Was studied in different populations covering entire Dioscorea growing forest area of the Jammu and Kashmir State. The mean, range, standard error and co-efficient of variation of twenty traits studied, revealed a great magnitude of variation amongst various populations. The underlying causes for such a huge variation are discussed.